Degradation of cellulose by basidiomycetous fungi - Baldrian, Petr; Valásková, Vendula (FEMS microbiology reviews, 2008)
Cellulose is the main polymeric component of the plant cell wall, the most abundant polysaccharide on Earth, and an important renewable resource. Basidiomycetous fungi belong to its most potent degraders because many species grow on dead wood or litter, in environment rich in cellulose. Fungal cellulolytic systems differ from the complex cellulolytic systems of bacteria. For the degradation of cellulose, basidiomycetes utilize a set of hydrolytic enzymes typically composed of endoglucanase, cellobiohydrolase and beta-glucosidase. In some species, the absence of cellobiohydrolase is substituted by the production of processive endoglucanases combining the properties of both of these enzymes. In addition, systems producing hydroxyl radicals based on cellobiose dehydrogenase, quinone redox cycling or glycopeptide-based Fenton reaction are involved in the degradation of several plant cell wall components, including cellulose. The complete cellulolytic complex used by a single fungal species is typically composed of more than one of the above mechanisms that contribute to the utilization of cellulose as a source of carbon or energy or degrade it to ensure fast substrate colonization. The efficiency and regulation of cellulose degradation differs among wood-rotting, litter-decomposing, mycorrhizal or plant pathogenic fungi and yeasts due to the different roles of cellulose degradation in the physiology and ecology of the individual groups.
Keywords: nemoci rostlin; Cellulase; Biodegradation, Environmental; biodegradace; rostliny; Plant Diseases; Cellulose; Hydroxyl Radical; hydroxylový radikál; benzochinony; Basidiomycota; celulasa; Benzoquinones; Plants; celulosa